Utility of Anti-Xa Monitoring in Children Receiving Enoxaparin for Therapeutic Anticoagulation - Leung, Marianna (Pediatric Pharmacy Advocacy Group, 2005)
Although enoxaparin is used to treat thromboembolism in children, current treatment guidelines are largely extrapolated from adults. The objectives of this study were to determine: i) correlation between enoxaparin dose and anti-factor Xa (anti-Xa) level, ii) intra-patient variability, and iii) whether dose or anti-Xa level is a predictor of outcomes. A retrospective chart review was conducted on all hospitalized patients receiving enoxaparin in a tertiary care pediatric institution. Simple linear regression, coefficient of variation (CV), and Student's t-test were used to analyze the objectives. Eighty treatment courses with interpretable anti-Xa levels were analyzed. Mean patient age was 6.5 years. Mean enoxaparin dose was 1.10 mg/kg q12h. Correlation between initial dosing and anti-Xa level was poor; R(2) = 0.0307 and 0.0237 for patients > 2 months with and without cardiac or renal diseases, respectively. Four out of seven patients ≤ 2 months of age compared to 4/32 patients > 2 months had a CV > 40%. Similarly, 4/12 cardiac patients compared to 4/27 non-cardiac patients had a CV > 40%. Neither dose nor anti-Xa level predicted treatment success or adverse reactions (P > .05). These results suggest a need to reexamine the use of anti-Xa levels for guiding enoxaparin therapy. Further prospective studies are warranted to clarify whether routine or selective anti-Xa monitoring should be recommended in pediatric patients.